Síntese e aplicação de nanofiltro contendo nanotubos de carbono na retenção de contaminantes em água - Nora, Robson Dalla (2015)
This work aimed to use Multiple Walls Nanotubes (MWNT) in order to synthesize a nanofilter to remove water contaminants and to test the nanofilter manufactured in removing Benzothiophene and pesticides present in water. The study was conducted in two stages. In the first step the nanofilter was developed and characterized. To develop the filter, the following materials were used: Chitosan, Polyethylene Glycol 6000 K, Sodium Hydroxide (NaOH), Sodium Dodecyl Sulphate (SDS), Acetic Acid Glacial and MWNT. To characterize the filter was performed: Scanning Electron Microscopy (SEM), Raman spectroscopy, the method of Brunauer, Emmett and Teller (BET) method Barrett, Joyner and Halenda (BJH) and permeate flow. In the second step, removal efficiency of benzothiophene and pesticides by the nanofilter was tested. For this experimental activity, it was split into two steps: filtering with benzothiophene and other pesticides. For filtering with benzothiophene, it was prepared a solution with a concentration of 0.79 ± 0.02 mmol in triplicate, where 5 samples were filtered with the same concentration of 3 similar nanofilters. For the filtering of pesticides, it was prepared one stock solution of 10.0 mL (1000.0 mg L-1) Imazapic, Imazethapyr, Imidacloprid, Ethyl Pirazolsulfuron). For pesticide analysis, it was used the Ultra Efficiency Liquid Chromatography coupled to Mass Spectrometry in series (UHPLC-MS / MS). The chromatographic conditions were established by LARP-UFSM. From the results obtained on the characterization, it can be said that the filter is characterized by low permeability and average pore radius of 15 A0. Carbon nanotubes are maintained after the manufacturing process and nanofilter may be used for removal of contaminants in water. As for the results of efficiency, nanofilter remove benzothiophene present in water with high efficiency. In addition, the nanofilter removes pesticides in water even at concentrations 10 times higher than those found in natural environment.